CROWNING GLORY: LIABILITY IN NEGLIGENCE OF PUBLIC AUTHORITIES REVISITED - Bowal, Peter; Boland, Lynn (Revue de droit de l'Université de Sherbrooke, 1994)
This article traces the development of the law which gradually permitted negligence actions to be brought against the Crown. The House of Lords decision in Anns has had a durable legacy in Canada. It calls for characterizing the sphere of government activity in question as either political (not reviewable) or operational (reviewable). The model is, nevertheless, unwieldy and lacks standards for predictable application. The Supreme Court of Canada had occasion recently in the cases of Brown and Swinamer to craft a more effective approach to the issue of negligence liability for public authorities, but failed to do so. The authors submit that these two cases merely affirm Canadian judicial policy to stay the Anns course for now, notwithstanding the attendant weaknesses and uncertainties of it.